Robotic Systems for general Surgery, Regulatory approvals and Market potential - Avgousti, Sotiris; Masouras, Panicos; Christoforou, Eftychios G.; Panayides, Andreas S.; Pattichis, Constantinos S. (My University, 2019)
In general surgery there exists a tendency towards less invasive procedures. With the use of laparoscopy, patients’ scarring and hospitalization periods have been considerably reduced. Furthermore, computer and robotics technologies have introduced novelties that enhance the surgeons’ skills to accomplish high precision during the complex surgery process. Robotic surgery became reality before the end of last century. Key developments include the Aesop voice-controlled camera-holding device and the Zeus robotic system, both by Computer Motion. A leading role has also been played by the company Intuitive Surgical, that developed the Da Vinci Surgical Robot. A master-slave system architecture was used in relation to both abovementioned robotic systems, where the surgeon is located at a console at the side of the operating table and controls the surgical instruments. The two companies merged in 2003 and the resulting Da Vinci Surgical Robot dominated the market. Other remarkable surgical robots have also been developed for applications including orthopedic surgery, stereotactic brain surgery and urological interventions. In United States, the development, testing and evaluation of any medical robotic device is controlled by the Food and Drug Administration (FDA). In Europe apply similar regulatory requirements but they are not identical and products are often required to comply with both. This study briefly describes the FDA regulatory approval process and discusses the current status of the medical robotic systems market, as well as the future trends. Some of the most important medical robotic systems that have been approved for clinical use are briefly described to show the current status and the potential of the medical robotics technology.
Keywords: ROBOTICS SYSTEMS; ROBOTICS SURGERY; FDA